2018
DOI: 10.1507/endocrj.ej17-0110
|View full text |Cite
|
Sign up to set email alerts
|

The synergic effect of BRAF<sup>V600E</sup> mutation and multifocality on central lymph node metastasis in unilateral papillary thyroid carcinoma

Abstract: Abstract. The purpose of this study is to evaluate the potential synergic effect of BRAF V600E mutation and multifocality on central lymph nodes metastasis (CLNM) in the patients with unilateral papillary thyroid carcinoma (PTC). We enrolled 413 patients with unilateral PTCs who accepted prophylactic unilateral or bilateral central lymph node dissection (LND). Univariate and multivariate analyses were made to determine the association between related factors and CLNM. Then, all patients were divided into 4 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…It was reported that tumor multifocality is not considered to be an independent risk factor of BRAF V600E mutation in PTC patients [ 30 ]. However, previous research also has demonstrated that BRAF V600E mutation is closely related to tumor multifocality with poor prognosis and aggressively behavior in PTC patients [ 31 ]. Our results showed that BRAF V600E mutation was related to multifocality in PTC patients which is analogous with previous research (OR = 1.22).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that tumor multifocality is not considered to be an independent risk factor of BRAF V600E mutation in PTC patients [ 30 ]. However, previous research also has demonstrated that BRAF V600E mutation is closely related to tumor multifocality with poor prognosis and aggressively behavior in PTC patients [ 31 ]. Our results showed that BRAF V600E mutation was related to multifocality in PTC patients which is analogous with previous research (OR = 1.22).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 14 retrospective studies and two prospective study from 2012 to 2023 were included in our review. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Most studies were performed in Asian countries including 11 from China, two from South Korea and one from Saudi Arabia. Basic information was demonstrated in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The potential role of BRAF mutation as a preoperative molecular marker of risk has reignited the issue. Many retrospective studies documented an association between BRAF mutation and lymph node metastases, [7][8][9][10][11][12][13][14] as well as a few prospective studies. 15 Kim et al 16 found an association only for PTC between 2 and 4 cm, as did Huang et al, 6 who proposed a TT for BRAF + solitary intrathyroidal PTC instead of a lobectomy as recommended by the American Thyroid Association guidelines.…”
Section: Discussionmentioning
confidence: 99%